PsycEXTRA Dataset 2012
DOI: 10.1037/e532162013-106
|View full text |Cite
|
Sign up to set email alerts
|

When Should We Disagree? The Effect of Conflict on Team Identity in North American and East Asian Teams

Abstract: Prior literature on conflict in teams has generally established that team heterogeneity (vs. homogeneity) influences the extent to which conflict occurs in teams. However, to date literature has not examined different types of culturally homogeneous teams' experience of team conflict and its effect on team identity. In two field studies, I look at the effect of team cultural composition and conflict on team identity (Study 1) and the effect of team cultural composition on the tendency to engage in conflict ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For example, diversity of team members' gender is positively associated with higher team performance in China but not in the US (Zhang & Hou, 2012). Similarly, Zhang and Tsui (2013) Liang et al (2014) found that team relationship conflicts had a weaker negative impact on team identity in East Asian student teams compared to North American ones, Cooper and Watson showed that relationship conflicts were negatively associated with team performance in more collectivistic, Mexican teams. One possibility is that despite sharing collectivistic cultural values, East Asians emphasize interdependent selfconstrual, while Mexicans tend to focus more on independent self-construal (Krys et al, 2022).…”
Section: Teamsmentioning
confidence: 99%
“…For example, diversity of team members' gender is positively associated with higher team performance in China but not in the US (Zhang & Hou, 2012). Similarly, Zhang and Tsui (2013) Liang et al (2014) found that team relationship conflicts had a weaker negative impact on team identity in East Asian student teams compared to North American ones, Cooper and Watson showed that relationship conflicts were negatively associated with team performance in more collectivistic, Mexican teams. One possibility is that despite sharing collectivistic cultural values, East Asians emphasize interdependent selfconstrual, while Mexicans tend to focus more on independent self-construal (Krys et al, 2022).…”
Section: Teamsmentioning
confidence: 99%